Serological evidence of Eastern equine encephalitis circulation in equids in Par? state, Brazil - Nunes, Josyn?lia do Socorro da Silva Sena (Sociedade de Medicina Veterin?ria do Rio de Janeiro, 2021)
Serum samples from 89 equids were analyzed (75 horses, 9 donkeys, and 5 mules) from the municipality of Viseu, Par? state, Brazil. Samples were collected in November 2014 and August 2015. The antibody prevalence against the following alphaviruses was estimated: Eastern equine encephalitis virus, Western equine encephalitis virus, Mucambo virus, and Mayaro virus. Seroprevalence was determined by the hemagglutination inhibition (HI) technique. Sera that exhibited HI antibodies with heterotypic reactions for the analyzed viruses were subjected to the 90% plaque reduction neutralization test (PRNT90). The HI prevalence of monotypic reactions to EEEV was 7.9%, and that of WEEV was 1.1%, as confirmed by PRNT90. Viral isolation attempts were negative for all tested blood samples. Our results suggest the circulation of equine encephalitis complex viruses. Future studies should evaluate the possible involvement of arthropod hosts and residents in the viral transmission in the study area